Oligofurostanosides-Furostanol Saponins. - SHARMA, S.C.; THAKUR, N.K.; CHAND, R. (Asian Journal of Chemistry, 2010)
Oligofurostanosides-the furostanol saponins with at least two sugar chains isolated till 1993 from various plants are reviewed along with their physical data. Latest chemical and spectroscopic techniques used for their isolation and characterisation have also been described.